A critical review on advanced molecular tools for bioremediation - Kumar, Sandeep; Dasila, Gunjan; Mahara, Kajal; Samant, Mukesh (Frontiers in Environmental Science, 2026)
Acceleration in environmental pollution driven by rapid industrialisation and urbanisation is burdening the ecosystem with various hazardous waste and effluents. Improper waste disposal practices have introduced various pollutants, including plastics, pesticides, heavy metals, polyaromatic hydrocarbons, and volatile organic compounds (VOCs), into atmospheric, terrestrial, and aquatic environments, thereby affecting agriculture, biodiversity, and human health. Acute toxicity, carcinogenicity, developmental toxicity, cardiovascular dysfunction, endocrine disruption, and nervous system damage are the major complications caused by environmental pollutants. The limitations of conventional chemical treatment methods highlight the need for biology-based alternatives. Being a cost-effective and eco-friendly solution, bioremediation utilises potential microbes to decontaminate the environment. Conventional bioremediation techniques, although efficient, have foundered in the complete elimination of pollutants, highlighting the need for a molecular approach for total mitigation. In this review, we have highlighted modern molecular techniques, such as Zinc Finger Nucleases (ZFNs), Transcription Activator-like Effector Nucleases (TALENs), and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR), that have revolutionised the process, facilitated efficient removal and promoted environmental sustainability. This review advances the field by framing bioremediation within contemporary global challenges such as heavy metal toxicity, microplastic accumulation, and pesticide persistence, and by emphasising iterative refinements through computationally derived gene delivery models that offer targeted, ecologically safer alternatives to conventional approaches. We have summarised the advancements in gene editing technology, which could be a more efficient technique for the remediation of various environmental pollutants.